CD-62°1346: An extreme halo or hypervelocity CH star? - Pereira, C. B. (2012)
High-velocity halo stars provide important information about the properties of the extreme Galactic halo. The study of unbound and bound Population II stars permits us to better estimate the mass of the halo. Aims: We carried out a detailed spectroscopic and kinematic study and have significantly refined the distance and the evolutionary state of the star. Methods: Its atmospheric parameters, chemical abundances and kinematical properties were determined using high-resolution optical spectroscopy and employing the local-thermodynamic-equilibrium model atmospheres of Kurucz and the spectral analysis code moog. Results: We found that CD-62°1346 is a metal-poor ([Fe/H] = -1.6) evolved giant star with Teff = 5300 K and log g = 1.7. The star exhibits high carbon and s-element abundances typical of CH stars. It is also a lead star. Our kinematic analysis of its 3D space motions shows that this star has a highly eccentric (e = 0.91) retrograde orbit with an apogalactic distance of ~100 kpc, exceeding by a factor of two the distance of the Magellanic Clouds. The star travels with very high velocity relative to the Galactocentric reference frame (VGRF = 570 km s-1). Conclusions: CD-62°1346 is an evolved giant star and not a subgiant star, as was considered earlier. Whether it is bound or unbound to the Galaxy depends on the assumed mass and on the adopted Galactic potential. We also show that the star HD 5223 is another example of a high-velocity CH star that exceeds the Galactic escape velocity. Possible origins of these two high-velocity stars are briefly discussed. CD-62°1346 and HD 5223 are the first red giant stars to join the restricted group of hypervelocity stars.